A solution-processed, mercaptoacetic acid-engineered CdSe quantum dot photocathode for efficient hydrogen production under visible light irradiation1. Issue 5 (6th May 2015) - Liu, Bin; Li, Xu-Bing; Gao, Yu-Ji; Li, Zhi-Jun; Meng, Qing-Yuan; Tung, Chen-Ho; Wu, Li-Zhu
<x xml:space="preserve">Abstract</x> We describe a simple, efficient and stable mercaptoacetic acid-engineered CdSe quantum dot photocathode for hydrogen generation by water-splitting from neutral water.